Entropy generation on flow and heat transfer of a reactive MHD Sisko fluid through inclined walls with porous medium. Issue 1 (31st December 2022) - Yusuf, T. A.; Naveen Kumar, R.; Punith Gowda, R. J.; Akpan, U. D.
Abstract : The present research focuses on flow, heat transfer, and entropy production properties in the context of their applications. The use of non-Newtonian materials in biomedical rheological models has garnered considerable attention. Having such practical and potential applications, the current study explores the incompressible, gravity-driven flow of a combustible Sisko liquid down inclined heated permeable walls embedded in a porous medium. The flow is said to be fully developed and modified Darcy's law is employed to express the porous medium. Such a flow is critical to simulate free-surface flows in trapezoidal reservoirs or channels, and around curved or inclined hulls. The spectral collocation technique with expansions in Chebyshev polynomials was instrumental in achieving numerical solutions. Furthermore, a parametric study is done to explore the behaviour of flow, thermal, entropy generation, and Bejan number profiles. The significant outcomes of the current study are that the rise in values of material parameter decreases the velocity, thermal, and entropy generation profiles but increases the Bejan number profile. The upsurge in values of magnetic parameter decreases the velocity and entropy generation profiles but increases the thermal and Bejan number profile. The rise in values of the Frank-Kameneskii parameter increases the thermal and entropy generation profiles.